Time-dependent and long-term mechanical properties of concretes incorporating different grades of coarse recycled concrete aggregates. (15th February 2018) - Gholampour, Aliakbar; Ozbakkaloglu, Togay
Highlights: The first study on the creep behavior and microstructure of recycled aggregate concrete (RAC) containing high-strength recycled aggregates is presented. Long-term compressive strength, elastic modulus, splitting tensile strength, workability, drying shrinkage, and creep of RACs are studied. Parent concrete strength of recycled aggregates significantly affects the time-dependent and long-term behavior of RACs. High-strength RACs containing 110-MPa recycled aggregates exhibit long-term properties that are similar to or better than those of companion conventional concrete. SEM and EDX analyses were performed to explain the mechanisms behind the mechanical test results. Abstract: It is now accepted that replacement of natural aggregates in concrete with recycled concrete aggregates obtained from construction and demolition waste is a promising technology to conserve natural resources and reduce the environmental impact of concrete. This paper presents a study on long-term properties of concretes manufactured with recycled aggregates of different parent concrete strengths. A total of six batches of recycled aggregate concretes (RACs) were manufactured. Tests were undertaken to establish the long-term compressive strength, elastic modulus, splitting tensile strength, workability, drying shrinkage, and creep of each batch. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) characterizations were performed to explain the mechanisms behind the observed time-dependent and mechanical properties of RACs. Test parameters comprised the replacement ratio and parent concrete strength of the recycled aggregates used in the preparation of the new concrete mixes. The results indicate that the parent concrete strength of the recycled aggregates significantly affects the time-dependent and long-term mechanical properties of RACs. It is shown that concrete mixes containing lower strength recycled concrete aggregates develop lower mechanical properties and higher shrinkage strain and creep deformation compared to mixes prepared with higher strength recycled concrete aggregates. Normal-strength RAC mixes containing higher strength recycled concrete aggregates develop slightly lower splitting tensile strength at all curing ages but similar compressive strength and elastic modulus in longer term (i.e. over 90 days) compared to those of the control mix. It is also shown that high-strength RACs, prepared with full replacement of natural aggregates with recycled concrete aggregates having a higher parent concrete strength, exhibit time-dependent and long-term mechanical properties that are similar to or better than those of companion natural aggregate concretes.